Simulated training of a laparoscopic vesicourethral anastomosis - Pinheiro,Eudes Fontenele Moraes (2018)
Abstract Purpose: To develop a model and curriculum for simulated training of an effective and well accepted laparoscopic vesicourethral anastomosis (VUA). Methods: Experimental longitudinal study of quantitative character. The sample consisted of 12 general surgery residents and 6 urology residents (R3). The training consisted of making twelve VUAs on synthetic organs. The training was divided into four sessions and accompanied by an instructor who performed positive feedback. The evaluation of the anastomoses considered the time and the analysis of the operative technique through the global evaluation scale Objective Structured Assessment of Technical Skills (OSATS). Results: Residents showed a reduction in operative time and evolution in the surgical technique statistically significant (p<0.01). The best-rated items were the facilitator positive feedback and the fact that the training was carried out at the teaching hospital premises. Conclusions: The proposed training model was well accepted and proved to be effective in reducing operative time and improving laparoscopic skills. The training should be fractionated (4 sessions in 3 weeks), repetitive (12 anastomoses) and have positive feedback.